Cardiac surgery considerations and lessons learned during the COVID‐19 pandemic. Issue 8 (15th July 2020) - Iribarne, Alexander; Thourani, Vinod H.; Cleveland, Joseph C.; Malaisrie, Sukit Christopher; Romano, Matthew A.; Moon, Marc R.; Ramakrishna, Harish; Mewhort, Holly E. M.; Halkos, Michael; Sultan, Ibrahim; Kindler, Christine; Firstenberg, Michael S.; et al.
Abstract: The COVID‐19 pandemic has transformed cardiac surgical practices. Limitations in intensive care resources and personal protective equipment have required many practices throughout the globe to pause elective operations and now slowly resume operations. However, much of cardiac surgery is not elective and patients continue to require surgery on an urgent or emergent basis during the pandemic. This continued need for providing surgical services has introduced several unique considerations ranging from how to prioritize surgery, how to ensure safety for cardiac surgical teams, and how best to resume elective operations to ensure the safety of patients. Additionally, the COVID‐19 pandemic has required a careful analysis of how best to carry out heart transplantation, extra‐corporeal membrane oxygenation, and congenital heart surgery. In this review, we present the many areas of multidisciplinary consideration, and the lessons learned that have allowed us to carry out cardiac surgery with excellence during the COVID‐19 pandemic. As various states experience plateaus, declines, and rises in COVID‐19 cases, these considerations are particularly important for cardiac surgical programs throughout the globe.